Transforming occupational health services provision in southern Africa through capacity building - Khoza, Norman; Chamdimba, Chimwemwe; Moyo, Dingani (Mettamedia (Pty) Ltd, 2022)
Africa boasts an expanse of diverse natural resources, notably minerals and agriculture. Almost every country is endowed with a specific natural resource that provides livelihoods to many. In tandem with the vast diversity of activities to tap these resources, a multiplicity of occupational exposures, some with far-reaching consequences, characterise the working environment across Africa. Most occupational diseases are under-reported due to poor diagnostic and management skills.1,2 Africa lags significantly in occupational health knowledge capital and institutional memory. Access to occupational health services, human capital in occupational health, and institutional memory at country levels is grossly deficient across most African countries.3,4 In most countries with near-absent specialists, occupational medicine expertise is very constrained; South Arica is the exception.1,3,5 Best practice standards in occupational health, including competency in the International Labour Office (ILO) International Classification of Radiographs of Pneumoconioses (ICRP), are lacking.